Synchronicity and firm interlocks in an emerging market☆ - Khanna, Tarun; Thomas, Catherine (Journal of Financial Economics, 2009)
Stock price synchronicity has been attributed to poor corporate governance and a lack of firm-level transparency. This paper investigates the association between different kinds of firm interlocks, control groups, and synchronicity in Chile. A unique data set containing equity cross-holdings, common individual owners, and director interlocks is used to map out firm ties and control groups. While there is a correlation between synchronicity and share ownership and equity ties, synchronicity is more strongly correlated with interlocking directorates. The presence of share directors is associated with either reduced firm-level transparency or increased correlation in firm fundamentals—due, for example, to joint resource allocation across the firms.